2011
DOI: 10.2350/10-07-0872-oa.1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Associations with a Placental Diagnosis of Delayed Villous Maturation: A Retrospective Study

Abstract: Delayed villous maturation (DVM) is a spectrum of placental disease characterized by decreased tertiary villus formation, reduced vasculosyncytial membrane formation, and, in its more severe forms, increased large bullous villi. In some series it has been associated with an increased risk of stillbirth in the late third trimester, but overall there are few data on its significance. The aim of this study was to assess perinatal factors associated with, and the clinical significance of, the finding of DVM on pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(41 citation statements)
references
References 17 publications
1
39
0
1
Order By: Relevance
“…19 Decreased placental maturation has been associated with gestational diabetes and perinatal death. 19,20 The association with the white matter/watershed and white matter/watershed injury with BGT involvement injury patterns suggests a role for antenatal, chronic hypoxia in these types of injury. In contrast, none of the placentas from infants with predominant BGT injury showed evidence of decreased maturation, supporting the hypothesis that severe chronic hypoxia is not a factor in this group.…”
Section: Discussionmentioning
confidence: 97%
“…19 Decreased placental maturation has been associated with gestational diabetes and perinatal death. 19,20 The association with the white matter/watershed and white matter/watershed injury with BGT involvement injury patterns suggests a role for antenatal, chronic hypoxia in these types of injury. In contrast, none of the placentas from infants with predominant BGT injury showed evidence of decreased maturation, supporting the hypothesis that severe chronic hypoxia is not a factor in this group.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, increased incidence of placental villous immaturity was commonly seen in placentas affected by pregestational (8, 32, 37) and GDM (10, 43). This placental abnormality, which has been independently associated with an increased risk of perinatal mortality (60), may serve as a connection between maternal diabetes and an increased risk of fetal intrauterine death (61). Further study in these areas is warranted to elucidate etiologic mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study, we have previously shown an association between DVM as defined qualitatively, and an adverse perinatal outcome 8 . We have also shown that DVM is not associated with antenatal ultrasound parameters 6 .…”
mentioning
confidence: 97%